2021
DOI: 10.1080/13102818.2020.1870871
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of miRNAs and their targets related to salt stress in Solanum lycopersicum H-2274

Abstract: The microRNAs (miRNAs) are a group of small non-coding RNAs found in both plants and animals. Their functions and target genes have been identified in many plant species. It has been shown that miRNAs have crucial roles in stress responses of plants as much as other defence mechanisms. Throughout abiotic stress, miRNAs regulate their target genes and take part in signalling pathways. In this study, we evaluated the expression profiles of miR156, miR170, miR171, miR395, miR398 and miR845, which have been shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…To determine whether the abiotic stress responses of SlHVA22 genes could also be related to miRNAs, we analyzed the miRNA target sites in SlHVA22 genes. Eleven out of fifteen SlHVA22 gene family members were targeted by tomato miRNAs that regulate abiotic stress tolerance in tomato, such as Sly-MIR159b , Sly-MIR166c-5p , Sly-MIR1917 , Sly-MIR395a , Sly-MIR396a , Sly-MIR396a-5p , Sly-MIR482a , Sly-MIR5302a , Sly-MIR5303 , Sly-MIR6023 , Sly-MIR6024 , Sly-MIR9470-5p , Sly-MIR9474-5p , Sly-MIR9479 , and sly-MIR9479-3p [ 29 , 30 , 31 , 32 ] ( Table S4 ). This indicates that many SlHVA22 genes might be linked to the post-transcriptional regulation of miRNAs in tomato abiotic stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether the abiotic stress responses of SlHVA22 genes could also be related to miRNAs, we analyzed the miRNA target sites in SlHVA22 genes. Eleven out of fifteen SlHVA22 gene family members were targeted by tomato miRNAs that regulate abiotic stress tolerance in tomato, such as Sly-MIR159b , Sly-MIR166c-5p , Sly-MIR1917 , Sly-MIR395a , Sly-MIR396a , Sly-MIR396a-5p , Sly-MIR482a , Sly-MIR5302a , Sly-MIR5303 , Sly-MIR6023 , Sly-MIR6024 , Sly-MIR9470-5p , Sly-MIR9474-5p , Sly-MIR9479 , and sly-MIR9479-3p [ 29 , 30 , 31 , 32 ] ( Table S4 ). This indicates that many SlHVA22 genes might be linked to the post-transcriptional regulation of miRNAs in tomato abiotic stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, one well-known drought response TF, Dof ( Li et al, 2021 ), might also regulate NtPOD93 ( Figure 4 ). Another example was miR395-NtPOD202-AP2 module, and many evidences suggested that both miR395 ( Kim et al, 2010 ; Çakır et al, 2021 ) and AP2 ( Zhang et al, 2009 ) might play important roles in salt treatment. Hence, the POD interaction network constructed in our study provides insights into the regulation of peroxides in plants in response to various stresses.…”
Section: Discussionmentioning
confidence: 99%